2009
DOI: 10.1007/s00330-009-1351-4
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive quantitation of human liver steatosis using magnetic resonance and bioassay methods

Abstract: The purpose was to evaluate the ability of three magnetic resonance (MR) techniques to detect liver steatosis and to determine which noninvasive technique (MR, bioassays) or combination of techniques is optimal for the quantification of hepatic fat using histopathology as a reference. Twenty patients with histopathologically proven steatosis and 24 control subjects underwent single-voxel proton MR spectroscopy (MRS; 3 voxels), dual-echo in phase/out of phase MR imaging (DEI) and diffusion-weighted MR imaging (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
101
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 25 publications
7
101
1
1
Order By: Relevance
“…Nevertheless, regional differences in HFF up to 12% obtained in the present study are not controversial to the biopsy results [13,25,26] .…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…Nevertheless, regional differences in HFF up to 12% obtained in the present study are not controversial to the biopsy results [13,25,26] .…”
Section: Discussioncontrasting
confidence: 51%
“…Szczepaniak et al [19] found a CV=11% for 10 subjects. The average CV calculated for spectroscopy volumes in three different positions was 12% for 20 steatosis patients and 24 control subjects [13] . Cowin et al [11] found different CV depending on volume position in the liver for a group of 6 subjects: CV=3% in right lobe, posterior; CV=7% in right lobe, anterior; CV=6% in right lobe, central; CV=13% in left lobe.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations